2015
DOI: 10.3389/fcimb.2015.00095
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations of PTPN2 and PTPN22: Role in the Pathogenesis of Type 1 Diabetes and Crohn's Disease

Abstract: Genome wide association studies have identified several genes that might be associated with increase susceptibility to Type 1 Diabetes (T1D) and Crohn's disease. Both Crohn's disease and T1D have a profound impact on the lives of patients and it is pivotal to investigate the genetic role in patients acquiring these diseases. Understanding the effect of single nucleotide polymorphisms (SNP's) in key genes in patients suffering from T1D and Crohn's disease is crucial to finding an effective treatment and generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 37 publications
1
70
0
4
Order By: Relevance
“…PTPN2 is a vitamin‐D‐responsive element that is believed to regulate the expression of inflammation‐related genes in diseases associated with the amplified proinflammatory state, such as diabetes mellitus, Crohn's disease and arthritis . However, decreased serum levels of 25VD 3 have been reported to be associated with the development of diabetes, Crohn's disease and chronic periodontitis, which indicates a potential regulatory relationship between PTPN2 and 25VD 3 .…”
Section: Discussionmentioning
confidence: 99%
“…PTPN2 is a vitamin‐D‐responsive element that is believed to regulate the expression of inflammation‐related genes in diseases associated with the amplified proinflammatory state, such as diabetes mellitus, Crohn's disease and arthritis . However, decreased serum levels of 25VD 3 have been reported to be associated with the development of diabetes, Crohn's disease and chronic periodontitis, which indicates a potential regulatory relationship between PTPN2 and 25VD 3 .…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] In humans, recent genome-wide association studies (GWASs) have identified the C1858T variant of PTPN22, which inhibits TCR-proximal signaling molecules such as Lck and ZAP-70, as a significant genetic risk factor for several autoimmune diseases including RA. [26][27][28][29] Among these various genetic alterations affecting T cell development and function, a Zap70 gene mutation found in SKG mice is unique in that it predominantly causes T cell-mediated autoimmune arthritis, enabling us to ask how the primary anomaly in T cells, not in tissue resident cells in the joint, causes autoimmune disease clinically and immunologically resembling human RA. 30,31 In this review, based on recent findings made with SKG mice, we discuss the molecular and cellular basis of how impaired TCRproximal signaling alters T-cell selection of conventional T cells (including arthritogenic autoimmune T cells) and Foxp3 + regulatory T (Treg) cells in the thymus and also respective functions in the pe-…”
Section: Introductionmentioning
confidence: 99%
“…41 This impaired selection of self-reactive B and T cells was found to reduce B and T cell receptor signaling, which may eventually result in autoimmunity. 42 Supporting this finding, Radenkovic et al 43 demonstrated a decreased frequency of Treg cells in LADA, which was considered to be an important component in activating cytokines for the cell-mediated immune responses. The results obtained in the present study are in accordance with those of earlier studies showing an association of the PTPN22 rs2476601 polymorphism with T1D and LADA.…”
Section: Discussionmentioning
confidence: 87%
“…Evidence suggests that the risk allele of PTPN22 reduces the elimination of naïve B cells expressing auto‐ and polyreactive antibodies in the bone marrow, whereas in T cells it affects the negative selection of regulatory T (Treg) cells in the thymus . This impaired selection of self‐reactive B and T cells was found to reduce B and T cell receptor signaling, which may eventually result in autoimmunity . Supporting this finding, Radenkovic et al demonstrated a decreased frequency of Treg cells in LADA, which was considered to be an important component in activating cytokines for the cell‐mediated immune responses.…”
Section: Discussionmentioning
confidence: 97%